Accounting Information System Analysis of Merchandise Inventory at PT Arnetha Jayapura - Chindy Junita Manurung; Winston Pontoh; Natalia Gerungai (Formosa Journal of Applied Sciences, 2023)
An accounting information system is a system that functions to carry out company data processing tasks by collecting data, changing data and providing quality information for users. This information is used to assist companies in making decisions and the existence of control elements in the accounting information system will be able to reduce the occurrence of errors and fraud. This research aims to find out how the accounting information system is implemented for merchandise inventory at PT Arnetha Jayapura. The results of the research show that the implementation of the accounting information system for merchandise inventory at PT Arnetha as a whole is quite good where work can be completed according to plan. However, there are still PT. Arnetha policies that are not appropriate, namely in terms of internal control, namely that there has not been a separation of functions between receiving goods and storage or warehouse, as well as recording inventory cards with the warehouse.